A proteção da criança refugiada, em especial através do reagrupamento familiar - Cristo, Natasha Bento (2018)
The intensification of the migration flows of children to the European Union since 2015 requires a more positive response from the Member States to adequately address the particular needs of these children, who were forced to leave their countries of origin with or without the company of a parent or other family member who has the child custody. Most of the children arriving in the EU are children who seek to escape situations of conflict that are widespread in their countries of origin and had previously experienced traumatic situations and abuse of their rights. In the light of EU law, most of these children are protected by the status of subsidiary protection, because they have not been individually persecuted and therefore, do not enjoy the refugee status. Many others qualify for the refugee status. The present dissertation deals with the inherent rights that come from international protection status, particularly the right to family reunification, when this is done in the best interests of the child. Member States are required to adopt a policy of non-discrimination on the basis of legal status, and there is therefore a need for greater protection of the right to family reunification compared with the protection that is currently provided to children that enjoy subsidiary protection status, as well as a flexible interpretation of the concept of family, beyond the nuclear family. The best interests of the child have to be taken into account in any decision concerning the child, whether it concerns family reunification or cases involving the expulsion of a child or of a family member from the host country.